The Wiley Handbook of Violence and Aggression 2017
DOI: 10.1002/9781119057574.whbva068
|View full text |Cite
|
Sign up to set email alerts
|

Training Staff to Manage Violence and Aggression

Abstract: People employed in a very wide range of occupations around the world can be exposed to violence in the course of their work. This chapter examines the issue of violence occurring in relation to the workplace and considers training as one element of a multidimensional approach to tackling the problem. It examines the concept of training and the diverse ways in which training programs tailored to specific occupations and settings have been developed. It then focuses on healthcare services, in particular where vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Therefore, in order to fulfil a basic human need, organisations should do their best to ensure a safe working environment. Although the effect of violence prevention training is debatable, our review found it to be essential, especially for new nurses, because training is the most effective and direct way to enhance employees' awareness, which is associated with violence prevention (Whittington & Price, 2017). Furthermore, postincident counselling is also needed as a significant intervention to mitigate the negative consequences of violence, a finding that is consistent with Hassankhani et al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to fulfil a basic human need, organisations should do their best to ensure a safe working environment. Although the effect of violence prevention training is debatable, our review found it to be essential, especially for new nurses, because training is the most effective and direct way to enhance employees' awareness, which is associated with violence prevention (Whittington & Price, 2017). Furthermore, postincident counselling is also needed as a significant intervention to mitigate the negative consequences of violence, a finding that is consistent with Hassankhani et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, organizational support, such as education and training programs, specific to the context of home care violence can help to prevent future incidents by equipping staff with relevant knowledge and skills (Whittington & Price, 2017). This is especially important in educating healthcare workers on when and how they can report violent incidents.…”
Section: Discussionmentioning
confidence: 99%